Photoluminescent Nanocrystals in a Multicomponent Aluminoborosilicate Glass - Ruivo, Andreia
In this study, stable and nonexpensive aluminoborosilicate glasses with different photoluminescence colors were synthesized by doping with Pb(II), Ba(II) and sodium halides. While glasses with NaF and NaCl exhibit no (or very low) luminescence, glasses doped with NaBr and NaI display room-temperature photoluminescence at 435 and 530 nm, respectively. The observed room-temperature photoluminescence is attributed to nanocrystals whose presence is revealed by transmission electron microscopy. The crystalline nature of the particles, which are pointed out as barium-lead halides, is also revealed by anisotropy measurements for Br and I doped samples. Time-resolved luminescence measurements show a second-order kinetics component combined with a first-order nonradiative rate constant. The photoluminescence properties here described are important for the future design of new optical materials or devices based on lead halide nanocrystals.